KNOWLEDGE AND PERCEPTION OF MARRIED MEN TOWARDS INFERTILITY AND ITS MANAGEMENT IN EDE NORTH LOCAL GOVERNMENT OSUN STATE, NIGERIA (2015)
Infertility is a public health problem that is characterised by serious social and psychological consequences. It is considered as a major life crisis that has the potential to threaten the stability of individuals and relationships, especially infertility among married men. Apart from the magnitude of the problem, management of infertility has focused more on women with little attention paid to men. The study was therefore designed to explore knowledge and perception of married men towards infertility and its management in Ede North Local Government Area (ENLGA), Osun State, Nigeria. A descriptive cross-sectional design was adopted including a survey, complemented with five Focus Group Discussions (FGD) sessions. For the survey, a purposive sampling technique was used to recruit married men from all the 11 wards in ENLGA. Data were collected using a pre-tested interviewer-administered questionnaire. The questionnaire elicited information on socio-demographic characteristics of respondents, knowledge, perception and management of infertility. Knowledge of infertility was measured on a 28-point scale with >17 rated as good, 10-17 as average and <10 as poor. Knowledge scores of the management of infertility on 16-point scale were rated as “poor” (<8) and “good” (≥8) respectively. Perception on infertility was measured on a 14-point scale and scores of <7 and ≥7 were classified as “wrong” and “right” respectively. Perception towards management of infertility was measured on a 12- point scale with <6 and ≥6 categorised “wrong” and “right”. Descriptive statistics and Chisquare test were used to analyse the quantitative data at p=0.05 while the FGD data were analysed using thematic approach. In all, 316 married men were interviewed. Age of the respondents was 40.1±10.3 (22-80) years, 98.7% were Yoruba, 69.0% were Muslims and 30.1% were Christians. About one-third (35.1%) of the respondents had secondary education and 43.0% were civil servants. Knowledge score of infertility was 18.4±2.8 with 65.5% of the respondents having good knowledge on infertility, while 71.8% had good knowledge of the management with the score of 8.4±2.2. Respondents with secondary education had average knowledge of infertility (18.5±2.9) compared to those that had primary education (17.8±2.4) and no formal education